The Misings: An Ethnographic Profile: Exploring the Unique Culture of the Mising Tribe in Assam (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India’s north east is known for its rich tribal cultures. Assam is inhabited by total twenty three numbers of notified tribe. Some of them have common origin while others had migrated from different places in different point of time. All of them have distinctly visible culture which makes this land a unique one. The rich heritage and colorfulness are a special feature of the North Eastern tribes. The Missing’s (in the Scheduled Tribe list of Assam referred as Miris) constitute the second largest group of Schedule tribes (Plains) of Assam. Missing’s inhabits in the far flung riverside areas of upper Assam with a population of 6,87,310 (census 2011). In this paper we are trying to present the ethnographic profile of the Mising tribe of Assam.